Cushing's syndrome. Issue 9996 (29th August 2015) - Lacroix, André; Feelders, Richard A; Stratakis, Constantine A; Nieman, Lynnette K
Summary: Chronic exposure to excess glucorticoids results in diverse manifestations of Cushing's syndrome, including debilitating morbidities and increased mortality. Genetic and molecular mechanisms responsible for excess cortisol secretion by primary adrenal lesions and adrenocorticotropic hormone (ACTH) secretion from corticotroph or ectopic tumours have been identified. New biochemical and imaging diagnostic approaches and progress in surgical and radiotherapy techniques have improved the management of patients. The therapeutic goal is to normalise tissue exposure to cortisol to reverse increased morbidity and mortality. Optimum treatment consisting of selective and complete resection of the causative tumour is necessay to allow eventual normalisation of the hypothalamic-pituitary-adrenal axis, maintenance of pituitary function, and avoidance of tumour recurrence. The development of new drugs offers clinicians several choices to treat patients with residual cortisol excess. However, for patients affected by this challenging syndrome, the long-term effects and comorbidities associated with hypercortisolism need ongoing care.